Analysis of Eco-Literacy in Online News Coverage of Plastic Waste Reduction Campaigns - Dorce Apriyurita; Fenny Yutika Seli (Jurnal Ilmiah Mandala Education (JIME), 2026)
This study examines the representation of ecological literacy in online news coverage of plastic waste reduction campaigns published by The Jakarta Post. Using a qualitative descriptive approach with content analysis, the study analyzed twelve English-language online news articles to identify how ecological literacy elements are embedded in environmental reporting. The analysis was guided by an ecological literacy framework focusing on five key dimensions: Ecological Knowledge, Environmental Awareness, Affective Engagement, Responsible Behavior, and Systematic Thinking. The findings indicate that ecological knowledge and environmental awareness are the most dominant dimensions, reflected through scientific explanations, problem-oriented narratives, and factual descriptions of the impacts of plastic waste. Meanwhile, affective engagement and systematic thinking appear less frequently due to the news' structural characteristics that prioritize objectivity and concise information. Responsible behavior is represented through descriptions of concrete environmental actions and sustainability initiatives. Overall, this study shows that online news serves not only as a source of information but also as an informal educational medium that contributes to increasing ecological literacy and environmental awareness. These findings highlight the important role of online journalism in supporting sustainability discourse and plastic waste reduction efforts in Indonesia.